Presence of a companion in the delivery room and breastfeeding in the first hour of life: is there an association? - Araujo, Larissa Ramos [UNESP]; Carvalhaes, Maria Antonieta de Barros Leite [UNESP]; Gomes, Caroline de Barros [UNESP] (FapUNIFESP (SciELO), 2023)
Objectives: to identify variables associated with the presence of a companion in the delivery room and its association with breastfeeding (BF) in the first hour of life. Methods: cross-sectional analysis of data from a cohort study (n=344). To investigate the factors associated with the presence of a companion during childbirth and breastfeeding in the first hour; we performed Poisson regression analyses, considering p<0.05 as the level of statistical significance. Results: 93.9% of the pregnant women had a companion in the delivery room, and no association was found between socioeconomic, obstetric and neonatal characteristics of the mother-child binomial and the presence of a companion. In a univariate analysis, the absence of a companion reduced the frequency of breastfeeding in the first hour (PR=0.64; CI95%=0.42-0.96), a result that was not confirmed in the adjusted analyses (PR=0.79; CI95%=0.54-1.15). Secondly, it was identified that the five minutes Apgar score was associated with first hour breastfeeding (PR=1.27; CI95%=1.14-1.40) regardless of the other factors. Conclusions: most women in the cohort had a companion in the delivery room, with no differences according to socioeconomic, obstetric and neonatal variables. The frequency of first hour breastfeeding was high; however, it was lower in the absence of a companion but this association was not independent of other factors.
Presença de acompanhante na sala de parto e aleitamento materno na primeira hora de vida: há associação?
Keywords: Breastfeeding; Infant; Pregnant women